FATHERING INFLUENCES PREDICT TEENAGER SMOKING ADDICTION - Ismah, Zata; Tanjung, Hazira Yulistia; Afifah, Sarah (Journal of Community Mental Health and Public Policy, 2025)
Background: In Medan City, 12.42% of adolescents aged 15-24 years, or approximately 48,311 teenagers, are smokers. Adolescents from broken homes are at a higher risk of psychological distres, which can lead to negative behaviors such as smoking. Purpose: To examine and analyze the level of smoking addiction among adolescents and how the father's role influences it. Method: A quantitative analytical survey with a cross-sectional design was conducted. The population consisted of high school students, with a sample of 1,221 adolescents who had lived in Medan for at least five years. The instruments used were the Game Addiction Scale for Adolescents (GASA) and the Fatherhood Scale 64 (FS-64). Statistical analysis included ANOVA, Pearson Correlation, and Chi-Square tests. Results: Fatherless adolescents were 3.06 times more likely to be light smokers compared to those with a positive father figure. A significant negative correlation was found, indicating that the higher the father's role score, the lower the level of smoking addiction. Conclusion: The lack of a father figure in a child's life contributes to smoking addiction. The stronger the father's role in a child's life, the lower the level of smoking addiction, and vice versa. Abstrak Latar Belakang: Di Kota Medan ditemukan remaja usia (15-24 tahun) yang merokok sebesar 12,42% atau sekitar 48.311 remaja di Kota Medan adalah seorang perokok. Remaja yang mengalami broken home sangat memicu peningkatan psikologis yang akhirnya akan menyebabkan remaja berperilaku negatif seperti merokok. Tujuan: Untuk menganalisis tingkat kecanduan rokok remaja serta bagaimana peran ayah mempengaruhinya. Metode: Survey analitik kuantitatif dengan desain cross sectional. Populasi adalah remaja yang sedang duduk di bangku SMA dengan sampel sebanyak 1221 remaja, dengan karakteristik remaja yang tinggal di Medan paling sedikit 5 tahun. Instrumen menggunakan Game Addiction Scale for Adolescents (GASA) dan Fatherhood Scale 64 (FS-64). Menggunakan statistik Anova, Korelasi Pearson dan Chi Square. Hasil: Anak Fatherless berisiko 3.06 kali merokok ringan dibandingkan pada remaja dengan peran ayah positif. Terdapat korelasi negatif signifikan dimana semakin tinggi skor peran ayah semakin rendah kecanduan merokok. Kesimpulan: Kurangnya peran ayah dalam kehidupan anak menyebabkan anak kecanduan merokok. Semakin tinggi peran ayah dalam hidup anak, maka semakin rendah tingkat kecanduan merokok pada anak, begitupun sebaliknya.